The Effect of Capital Structure and Profitability on Firm Value with Inflation Rate as Moderating Variable in Food and Beverage Companies on the Indonesia Stock Exchange - Burhanuddin; Guasmin; Rajindra (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine the effect of capital structure and profitability on firm value moderated by the inflation rate, using a sample of food and beverage companies on the IDX. Based on the results of the analysis, capital structure has a negative and insignificant effect on firm value, while profitability has a positive and significant effect on firm value. Inflation rate cannot moderate the effect of capital structure on firm value, but it can give positive and insignificant impact on the effect of capital structure on firm value. Likewise, the inflation rate cannot moderate the effect of profitability on firm value and has a negative and insignificant impact on the effect between these variables.